INFLUENCE OF CITY BRANDING, BRAND IDENTITY AND BRAND IMAGE ON VISITING DECISION TO KOTA PEKALONGAN - Ujianto Purwanto; Euis Soliha (Jurnal Bisnis Manajemen, 2017)
Recently, city branding become the most issue in marketing. The cities being developed to be the best destination for tourism, therefore, by city branding, it was not only to attract the tourist for visiting the city but also to make the city image. Regarding for this, Pekalongan city that had huge potential in batik, in the first april as the pekalongan 105  anniversary had launched the city branding for Pekalongan by the tag line "world's city of batik", it meant that pekalongan is a city for batik in the world. This research was conducted by respondent survey to analyze the influence of city branding to the decision for visiting Pekalongan city. Respondents were the visitors of mega event "Batik Pekalongan International Week 2013" in 2-4 October 2014. The respondent were the visitor of “Pekalongan Batik Week International 2013” in 23-24 October 2014. The research was conducted by using a survey design. Respondent were choosen by purposive sampling in the some condition that the visitor are adult, minimally senior high school graduated and having income. From the 125 surveyed respondent, 81(64.8%) were not Pekalongan people. Analysis methods of this study were multiple linear regression analysis, F test, t test, and path analysis (mediation test). The result showed that city branding did not directly influence to the decision for visiting Pekalongan. City branding had effects on decision for visiting pekalongan through the mediation of making brand identity and brand image.